Predictors of left ventricular ejection fraction in high-risk percutaneous coronary interventions - Panoulas, Vasileios F.; Escaned, Javier; Hill, Jonathan M.; Barker, Erin; Butler, Karin; Almedhychy, Ali; Tsintzos, Stelios I.; O’Neill, William W. (Frontiers in Cardiovascular Medicine, 2024)
Revascularization completeness after percutaneous coronary intervention (PCI) is associated with improved long-term outcomes. Mechanical circulatory support (intra-aortic balloon pump [IABP] or Impella) is used during high-risk PCI (HR-PCI) to enhance peri-procedural safety and achieve more complete revascularization. The relationship between revascularization completeness (post-PCI residual SYNTAX Score [rSS]) and left ventricular ejection fraction (LVEF) in HR-PCI has not been established. We investigated LVEF predictors at 90 days post-PCI with Impella or IABP support. Individual patient data (IPD) were analyzed from PROTECT II (NCT00562016) in the base case. IPD from PROTECT II and RESTORE-EF (NCT04648306) were naïvely pooled in the sensitivity analysis. Using complete cases only, linear regression was used to explore the predictors of LVEF at 90 days post-PCI. Models were refined using stepwise selection based on Akaike Information Criterion and included: treatment group (Impella, IABP), baseline characteristics (age, gender, race, New York Heart Association Functional Classification, LVEF, SYNTAX Score [SS]), and rSS. Impella treatment and higher baseline LVEF were significant predictors of LVEF improvement at 90 days post-PCI (p≤0.05), and a lower rSS contributed to the model (p=0.082). In the sensitivity analysis, Impella treatment, higher baseline LVEF, and lower rSS were significant predictors of LVEF improvement at 90 days (p≤0.05), and SS pre-PCI contributed to the model (p=0.070). Higher baseline LVEF, higher SS pre-PCI, lower rSS (i.e. completeness of revascularization), and Impella treatment were predictors of post-PCI LVEF improvement. The findings suggest potential mechanisms of Impella include improving the extent and quality of revascularization, and intraprocedural ventricular unloading.